The Influence Of Leadership And Kaizen Culture Through Work Environment On Employee Performance At The Regional Revenue Agency Of Badung Regency - I Gede Yoby Negara; Ni Luh Putu Agustini Karta; Ni Ketut Dewi Irwanti (UNIVERSITAS PAKUAN, 2025)
The objective of this study was to analyze the influence of leadership and kaizen culture on the work environment, with the aim of understanding its effect on employee performance at the Badung Regency Regional Revenue Agency. The population of this study comprised all employees of the Badung Regency Regional Revenue Agency, with a total of 262 individuals. The sample size was determined to be 72 individuals. The technique employed to determine the respondents in this study was random sampling. A questionnaire was utilized as a data collection instrument. The research analysis technique employed included validity tests, reliability tests, classical assumption tests, and path analysis tests. The findings of this study indicated that leadership, the work environment, and kaizen culture exerted a positive and significant influence on employee performance at BAPEDA Badung Regency. However, the work environment failed to function as a mediating variable in the relationship between kaizen culture and employee performance at BAPENDA Badung Regency. The study posits that the Badung Regency Regional Revenue Agency has the potential to enhance its leadership, kaizen culture, work environment, and employee performance.